Phenotypic plasticity in the response of sorghum to water stress and recovery indicates pre-flowering drought tolerance - Miller, Sarah Bethany, author; Jahn, Courtney, advisor; Argueso, Cris, committee member; Broeckling, Corey, committee member; Leach, Jan, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.
Zip file contains data spreadsheet.
Keywords: morphology; plasticity; sorghum; physiology; drought; root exudation